2010
DOI: 10.21273/hortsci.45.4.707
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Quality Attributes of Four Fresh Fig (Ficus carica L.) Cultivars Harvested at Two Maturity Stages

Abstract: The effect of two fruit maturity stages on the quality attributes of four fresh fig cultivars was examined, including consumer acceptance and antioxidant capacity. Fig quality attributes such as weight, soluble solids concentration (SSC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
80
8
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(106 citation statements)
references
References 25 publications
15
80
8
3
Order By: Relevance
“…These findings are similar to those obtained by other authors for main crop figs for accession 'KZTP-38' (Ş imş ek and Yildirim, 2010) Table 4 Pomological and quality characteristics of the breba and main crops of the six fig cultivars during the studied period (2011)(2012)(2013) Neck length (mm) 13 ± 4 c 11.7 ± 5 d 14.5 ± 4.8 b 10.2 ± 3.8 e 36.1 ± 7.8 a 9.5 ± 3.4 e 0 *** * ns Ostiole width (mm) 7.1 ± 2.8 d 11.7 ± 3.6 a 8.1 ± 2.2 c 8.5 ± 4.5 c 6.6 ± 2.3 e 10.2 ± 2.3 b 0 *** *** ** TSS ( • Brix) 18.7 ± 2.6 a 16.4 ± 1.1 d 18.1 ± 1.7 b 16.6 ± 1.2 d 15.6 ± 1.4 e 17.6 ± 1.7 c 0 *** *** *** pH 6.0 ± 0.3 a 5.7 ± 0.3 b 5.5 ± 0.3 c 5.7 ± 0.2 b 5.6 ± 0.4 d 5.3 ± 0.4 e 0 *** *** *** TA (g citric acid 100 g −1 fresh weight) 0.1 ± 0.03 d 0.1 ± 0.02 d 0.1 ± 0.04 c 0.1 ± 0.02 d 0.2 ± 0.05 b 0.2 ± 0.05 a 0 *** ** *** Firmness N mm −1 1.1 ± 0.5 d 1.3 ± 0.6 b 1.5 ± 0.6 a 1.2 ± 0.5 c 1.5 ± 0.7 a 1.2 ± 0.6 c 0 and for the cultivar 'Bursa Siyahi' (Ç aliskan and Polat, 2012), which are several genotypes grown in Turkey. Nevertheless, these findings are in contrast to those obtained by Crisosto et al (2010) for these cultivars grown in California. In the case of the 'Cuello Dama Blanco', 'Brown Turkey', and 'Colar Elche' cultivars, the values obtained in the present study for fruit weight were higher than those obtained by Crisosto et al (2010).…”
Section: Morphological Analysiscontrasting
confidence: 99%
See 3 more Smart Citations
“…These findings are similar to those obtained by other authors for main crop figs for accession 'KZTP-38' (Ş imş ek and Yildirim, 2010) Table 4 Pomological and quality characteristics of the breba and main crops of the six fig cultivars during the studied period (2011)(2012)(2013) Neck length (mm) 13 ± 4 c 11.7 ± 5 d 14.5 ± 4.8 b 10.2 ± 3.8 e 36.1 ± 7.8 a 9.5 ± 3.4 e 0 *** * ns Ostiole width (mm) 7.1 ± 2.8 d 11.7 ± 3.6 a 8.1 ± 2.2 c 8.5 ± 4.5 c 6.6 ± 2.3 e 10.2 ± 2.3 b 0 *** *** ** TSS ( • Brix) 18.7 ± 2.6 a 16.4 ± 1.1 d 18.1 ± 1.7 b 16.6 ± 1.2 d 15.6 ± 1.4 e 17.6 ± 1.7 c 0 *** *** *** pH 6.0 ± 0.3 a 5.7 ± 0.3 b 5.5 ± 0.3 c 5.7 ± 0.2 b 5.6 ± 0.4 d 5.3 ± 0.4 e 0 *** *** *** TA (g citric acid 100 g −1 fresh weight) 0.1 ± 0.03 d 0.1 ± 0.02 d 0.1 ± 0.04 c 0.1 ± 0.02 d 0.2 ± 0.05 b 0.2 ± 0.05 a 0 *** ** *** Firmness N mm −1 1.1 ± 0.5 d 1.3 ± 0.6 b 1.5 ± 0.6 a 1.2 ± 0.5 c 1.5 ± 0.7 a 1.2 ± 0.6 c 0 and for the cultivar 'Bursa Siyahi' (Ç aliskan and Polat, 2012), which are several genotypes grown in Turkey. Nevertheless, these findings are in contrast to those obtained by Crisosto et al (2010) for these cultivars grown in California. In the case of the 'Cuello Dama Blanco', 'Brown Turkey', and 'Colar Elche' cultivars, the values obtained in the present study for fruit weight were higher than those obtained by Crisosto et al (2010).…”
Section: Morphological Analysiscontrasting
confidence: 99%
“…Nevertheless, these findings are in contrast to those obtained by Crisosto et al (2010) for these cultivars grown in California. In the case of the 'Cuello Dama Blanco', 'Brown Turkey', and 'Colar Elche' cultivars, the values obtained in the present study for fruit weight were higher than those obtained by Crisosto et al (2010). These differences could be explained by the different growth conditions (Ç aliskan and Polat, 2008).…”
Section: Morphological Analysiscontrasting
confidence: 99%
See 2 more Smart Citations
“…Orchard sprays with gibberellic acid significantly reduced fruit weight loss and decay during subsequent storage (Amen, 1987). Recent research demonstrated that fig genotype and maturity stage influence fruit quality (Crisosto et al, 2010).…”
Section: Quality Characteristics and Criteriamentioning
confidence: 99%